2018
DOI: 10.3389/fonc.2018.00617
|View full text |Cite|
|
Sign up to set email alerts
|

Metabolic Dependencies in Pancreatic Cancer

Abstract: Pancreatic ductal adenocarcinoma (PDA) is a highly lethal cancer with a long-term survival rate under 10%. Available cytotoxic chemotherapies have significant side effects, and only marginal therapeutic efficacy. FDA approved drugs currently used against PDA target DNA metabolism and DNA integrity. However, alternative metabolic targets beyond DNA may prove to be much more effective. PDA cells are forced to live within a particularly severe microenvironment characterized by relative hypovascularity, hypoxia, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 104 publications
1
80
0
Order By: Relevance
“…Specifically, pancreatic cancer is a disease that could greatly benefit from mitochondrial metabolism targeting [1][2][3][4][5]. The most frequent pancreatic cancer is Pancreatic Ductal AdenoCarcinoma (PDAC), the fifth leading cause of cancer death in the United States by 2017 [6] and the 13th worldwide by 2018 [7].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, pancreatic cancer is a disease that could greatly benefit from mitochondrial metabolism targeting [1][2][3][4][5]. The most frequent pancreatic cancer is Pancreatic Ductal AdenoCarcinoma (PDAC), the fifth leading cause of cancer death in the United States by 2017 [6] and the 13th worldwide by 2018 [7].…”
Section: Introductionmentioning
confidence: 99%
“…This suggests DNAJA1 skews BxPC-3 towards alanine production while MIA PaCa-2 is directed to lactate. Investigations into PDAC cellular communication has shown that stellate cells provide alanine to pancreatic cancer cells in order to promote tumor progression and metastasis (20). This increase in alanine in D1-Bx supports increased cellular invasion and survival, which is discussed further in the following sections.…”
Section: Dnaja1 Alters the Rate Of Aerobic Glycolysis And Diversifiesmentioning
confidence: 78%
“…In these D1 cells, we observed significant dysregulation in fundamental metabolic pathways, marginal loss of mitochondrial dispersion, and loss of lysosomal integrity, which collectively impacted cellular survival. DNAJA1 overexpression exhibits a distinct impact on tumor specific metabolic processes like aerobic glycolysis and glutaminolysis, which is coupled with a response specific to the two phenotypically unique pancreatic cancer cells (8,19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Nutrient provision by altered metabolic pathways is another important aPSC contribution to PaCa cell progression. This proceeds through increased glycolysis, amino acid (AA) production from protein degradation, by glycosylation and fatty acid synthesis, called the metabolic switch (507). Accordingly, glycolytic enzymes such as hexokinase-2, enolase-2, LDHA, and B 1 (508) and glycolytic metabolites are elevated (509).…”
Section: Activated Pancreatic Stellate Cells and The Crosstalk With Tmentioning
confidence: 99%